2005
DOI: 10.1021/jp054576s
|View full text |Cite
|
Sign up to set email alerts
|

DFT and In Situ EXAFS Investigation of Gold/Ceria−Zirconia Low-Temperature Water Gas Shift Catalysts:  Identification of the Nature of the Active Form of Gold

Abstract: A combined experimental and theoretical investigation of the nature of the active form of gold in oxide-supported gold catalysts for the water gas shift reaction has been performed. In situ extended X-ray absorption fine structure (EXAFS) and X-ray absorption near-edge structure (XANES) experiments have shown that in the fresh catalysts the gold is in the form of highly dispersed gold ions. However, under water gas shift reaction conditions, even at temperatures as low as 100 degrees C, the evidence from EXAFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
245
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(266 citation statements)
references
References 53 publications
18
245
2
1
Order By: Relevance
“…For each spectrum, the gas phase CO was subtracted from the original spectra recorded during the reaction. During thermal activation at 150 °C, the predominant feature was the band at 2095 cm −1 associated with the CO adsorbed on Au 0 , specifically at the step sites or the perimeter of Au nanoparticles, consistent with previous studies 23, 27, 34. A small contribution of Au δ+ −CO species at 2120 cm −1 was also observed.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…For each spectrum, the gas phase CO was subtracted from the original spectra recorded during the reaction. During thermal activation at 150 °C, the predominant feature was the band at 2095 cm −1 associated with the CO adsorbed on Au 0 , specifically at the step sites or the perimeter of Au nanoparticles, consistent with previous studies 23, 27, 34. A small contribution of Au δ+ −CO species at 2120 cm −1 was also observed.…”
supporting
confidence: 91%
“…The calculated specific energy input for an applied voltage of 7 kV was 9.2 W. No change in the selectivity was observed for the different voltages tested or under thermal conditions. In all cases, the reaction was selective to CO 2 , with mass balances of 97 %±3 % (Table S1) which is consistent with the previous studies under thermal control 22, 23. Furthermore, temperature‐programmed oxidation of the used samples confirmed that little carbon deposition took place and that the carbon‐containing species evolution could be attributed to carbonate decomposition after both thermal and plasma reactions24 (Figure S3).…”
supporting
confidence: 88%
See 3 more Smart Citations